Serological and molecular evaluation of Senecavirus A (SVA) in pigs from farrow-to-finish farms in Minas Gerais, Brazil - Júnio César Santos; Emelly Barbosa Calheiros; Leonardo Teófilo Toledo; Ugonna Henry Uzoka; Fernanda Simone Marks; Wagnner José Nascimento Porto; Alessandra Abel Borges; João Alberto Farinelli Pantaleão; Maria Isabel Isabel Maldonado Coelh Guedes; Carlos Eduardo Real Pereira; David Germano Goncalves Schwarz; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2026)
The emergence of Senecavirus A (SVA) as a causative agent of vesicular diseases in pigs is noteworthy, since it was identified in 2014 through outbreaks in Brazil. The SVA belongs to the Picornaviridae family and is a non-enveloped virus with the ability to adapt to the environment. As the virus’s stability allows it to persist on farms post-outbreak, maintaining stringent biosecurity measures is crucial for effective control. This study aims to evaluate antibody response and viral RNA shedding in swine farms. Blood and fecal samples were collected from pigs in 2022 on farms that experienced outbreaks in 2015 and 2016. The sampled pigs were from farrow-to-finish farms without clinical signs of SVA obtained from five farms in Minas Gerais state, Brazil, covering all production phases: sows, farrowing, nursery piglets, growing, and finishing pigs. Real-time PCR and serum neutralization tests were conducted. Antibodies against SVA were detected in all production phases from four of the positive farms, with sows showing the highest antibody prevalence. Viral RNA was found in fecal samples from two farms, with the farrowing phase pigs exhibiting the highest viral RNA positivity. These findings indicate the presence of SVA infection on farms with no clinical signs, suggesting that the virus may have persisted following previous outbreaks due to its environmental stability. This study provides a comprehensive profile of antibody and viral RNA presence across different production phases, which may be applicable for informing biosafety measures.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Interactions between Mycoplasma hyopneumoniae strains and the resident lung microbiota in swine - Leonardo Teófilo Toledo; Richard Costa Polveiro; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira; Fernanda Simone Marks (Veterinary Microbiology, 2026)